Microbial analysis of leachate using Fluorescent In Situ Hybridization (FISH) technique to evaluate the landfill stability - (:unkn) unknown (My University, 2005)
Since, landfilling of municipal solid wastes is still insufficient in Turkey, construction of new well-engineered landfills and remediation of unregulated dumping sites are urgently required. To enhance the stabilization in existing dumping sites and new landfills, the relationship between the landfill microbiology and stabilization should be certainly well understood. Therefore, in this study, in addition to chemical characterization and methane potential assays, microbial analysis of leachate with fluorescent in-situ hybridization were used in the evaluation of landfill stabilization. FISH analysis indicated that there was an obvious correlation between the landfill stability and abundance of acetate utilizing methanogens. While, stringent Methanosarcina clusters, which favor high acetate concentration were found predominant in young landfill leachates, Methanosaeta was the major methanogenic community in mature samples containing quite low methane potentials and BOD/COD ratios. Likewise, the numbers of beta-Proteobacteria significantly declined in mature landfill leachates. On the other hand, dissimilarities with previous studies revealed that the microbial diversity differs from landfill to landfill as well as in different stabilization phases. Overall, the results suggested that in situ hybridization technique is likely to become a favored method for routine analysis in evaluation of landfill stability. © by PSP 2005.
Keywords: FISH; Landfill; Leachate; Methane potential; Methanosarcina; Stabilization